2004
DOI: 10.1172/jci22098
|View full text |Cite
|
Sign up to set email alerts
|

β cell replication is the primary mechanism for maintaining postnatal β cell mass

Abstract: The endocrine pancreas undergoes major remodeling during neonatal development when replication of differentiated β cells is the major mechanism by which β cell mass is regulated. The molecular mechanisms that govern the replication of terminally differentiated β cells are unclear. We show that during neonatal development, cyclin D2 expression in the endocrine pancreas coincides with the replication of endocrine cells and a massive increase in islet mass. Using cyclin D2 -/-mice, we demonstrate that cyclin D2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
393
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(437 citation statements)
references
References 28 publications
38
393
3
3
Order By: Relevance
“…The fact that this was present in a man 89 years of age shows that there is a lifelong capacity to induce beta cell replication in humans. This finding is also consistent with findings in mice using lineage tracing [17] and cyclin D2 deletion [18], which identified beta cell replication as the primary mechanism for postnatal beta cell expansion.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that this was present in a man 89 years of age shows that there is a lifelong capacity to induce beta cell replication in humans. This finding is also consistent with findings in mice using lineage tracing [17] and cyclin D2 deletion [18], which identified beta cell replication as the primary mechanism for postnatal beta cell expansion.…”
Section: Discussionsupporting
confidence: 91%
“…The involvement of CCND1 protein in beta cell proliferation has recently been verified by others: overexpression of either Ccnd1 alone or in combination with Cdk4-induced beta cell proliferation in rat and human pancreatic islets [23], and CCND1 protein was shown to be essential for normal postnatal pancreatic beta cell growth [24]. These studies, together with our results, implicate CCND1 protein in beta cell proliferation, although CCND2 was also reported to trigger the progression of beta cell replication in the early postnatal period [24,25]. We clearly demonstrated that the induction of Ccnd1 expression by exendin-4 occurred predominantly at the transcriptional level.…”
Section: Discussionsupporting
confidence: 87%
“…According to these findings, both in vivo-and in vitro-enhanced ␤ cell proliferation seemed to be due to the direct effect of CXCL10 neutralization, although more detailed studies are required to clarify this. Moreover, these results of the present study in which enhanced ␤ cell proliferation by CXCL10 neutralization maintained the ␤ cell mass, resulting in suppression of the onset of diabetes, are consistent with recent reports by others that replication of differentiated ␤ cells is essential to maintain the ␤ cell mass (43,44). Not only in type 1 diabetes, but also in type 2 diabetes, it has been suggested that a reduction in ␤ cell mass is one of the most important factors in disease progression; therefore, CXCL10 neutralization may be useful for maintaining the ␤ cell mass in both types of diabetes.…”
Section: Discussionsupporting
confidence: 93%